Pengaruh Suplementasi Saccharomyces cerevisiae Sebagai Probiotik Dalam Ransum Berbasis Pakan Lokal Terhadap Performans Dan Kecernaan Nutrisi Pada Babi Lokal Fase Starter - Johanis Ly; Novallino H. G. Kallau (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The long term purposes of the study are to change the mind and the custom of pigs farmers from using restaurant or household wastes to using local feeds enriched with yeast (Saccharomyces cerevisiae). The short term or special purpose of the study are to find out the cheaper alternative feeds for pigs and information of using yeast to improve feeds quality and pigs productivity. The study with those purposes was carried out off farm by supplementing yeast into low quality pig feeds (crude protein/CP ≤ 16%) of local weaned pigs composed of: corn meal, rice brand, soybean/tofu extract and unused fish meal. 12 local weaned pigs were fed 4 treatment diets based on block design of 4 treatments with 3 blocks design procedure. The 4 treatment feeds were formulated as : R0 (commercial diet/551); R1 (basal feed + 2% yeast of daily requirement); R2 (basal feed + 4% yeast of daily requirement); and R3 (basal feed + 6% yeast of daily requirement). Feed intake, daily weight gain, feeds conversion efficiency, protein, and crude fibre digestibility were studied in the study. Statistical analysis showed that the effect of the treatments is not significant (P>0.05) on all variables studied. Supplementation yeast of 6% is the best treatment performing the highest result of most variable studied. The conclusion drawn is that supplementing yeast up to 6% could improve performance of weaned pigs fed low quality feed and perform the similar result with feeding commercial feed (551). It is suggested to use yeast up to 6% in the diet and further research including widen range and high level of yeast supplementation could be done.